Quantifying the Impacts of Failures of Departments of Transportation Building Systems on Road System Users. Issue 1 (January 2014) - Gatti, Umberto C.; El-Anwar, Omar; Migliaccio, Giovanni C.; Lin, Ken-Yu; Medina, Yvonne
Because of the financial crisis of 2007 to 2008 and the subsequent economic downturn, funding for transportation agencies has been consistently reduced. This lack of funds prevents the building assets of transportation agencies from being efficiently maintained, so failures may occur that discontinue employees' operations and activities and affect transportation system users. Thus, to maximize the use of available funding, it is compelling to create innovative tools and techniques capable of estimating how potential failures can affect employees' activities and, eventually, transportation system users. Facility managers and decision makers could use such estimates to make decisions on maintenance of building assets that would minimize the risks of disruptions to employees and transportation system users. Among the capital assets of the Washington State Department of Transportation (DOT), transportation equipment fund (TEF) shops are crucial in ensuring timely and effective care and maintenance of the majority of state vehicles and equipment. Therefore, any disruption of the operations of TEF shop facilities could significantly affect not only the Washington State DOT's vehicles and equipment maintenance but also the department's ability to fulfill its core mission. Given the importance of TEF shops, this exploratory case study investigates the failures that have occurred or are likely to occur in these facilities and employs discrete-event simulation to quantify the consequences of such failures on the shop activities and road users.